Augmented reality for industrial robot programmers: Workload analysis for task-based, augmented reality-supported robot control - Stadler, Susanne; Kain, Kevin; Giuliani, Manuel; Mirnig, Nicole; Stollnberger, Gerald; Tscheligi, Manfred (IEEE RO-MAN, 2016)
Augmented reality (AR) can serve as a tool to provide helpful information in a direct way to industrial robot programmers throughout the teaching process. It seems obvious that AR support eases the programming process and increases the programmer's productivity and programming accuracy. However, additional information can also potentially increase the programmer's perceived workload. To explore the impact of augmented reality on robot teaching, as a first step we have chosen a Sphero robot control scenario and conducted a within-subject user study with 19 professional industrial robot programmers, including novices and experts. We focused on the perceived workload of industrial robot programmers and their task completion time when using a tablet-based AR approach with visualization of task-based information for controlling a robot. Each participant had to execute three typical robot programming tasks: tool center point teaching, trajectory teaching, and overlap teaching. We measured the programmers' workload in the dimensions of mental demand, physical demand, temporal demand, frustration, effort, and performance. The study results show that the presentation of task-based information in the tablet-based AR interface decreases the mental demand of the industrial robot programmers during the robot control process. At the same time, however, the programmers' task completion time increases.